Effect of Tourniquet Use During Ankle Fracture Fixation on Wound Healing and Infectious Complications. (June 2020) - Benedick, Alex; Rivera, Trenton; Vallier, Heather A.
Background: Tourniquets are common during extremity surgery; however, effects of tourniquets on complications following ankle fracture surgery have not been well described. The purpose was to evaluate effects of tourniquet usage on wound complications and infections after ankle fracture fixation. Methods: Consecutive patients (N = 903) treated operatively for torsional ankle injury were identified. Patients for whom a tourniquet was used intraoperatively (n = 523) were compared to those without (n = 380). Subgroup analysis included patients possibly sensitive to tissue ischemia (diabetes, obesity, tobacco, age >65 years, and open fracture). Multiple logistic regression analysis was performed. Results: A tourniquet was used in 523 (57.9%) of cases. Overall, 22.9% of patients had open fractures in the group with no tourniquet, vs 11.3% ( P < .001), with no differences in fracture pattern or medical comorbidities, except tobacco use was more frequent in the no tourniquet group (51.9% vs 44.4%, P = .032). No significant differences in complications were noted, including superficial infection (4.2% [no tourniquet] vs 5.2%), deep infection (2.1% vs 2.3%), and wound healing problems (6.3% vs 4.0%). Similarly, subgroup analysis failed to reveal any differences in complications based on diabetes, obesity, tobacco use, age, or open fracture. However, patients with open fractures or diabetes were more likely to experience deep infection (OR 3.73, P = .014, and OR 4.01, P = .021, respectively). Conclusions: Tourniquet use did not affect rates of wound healing problems or infections. However, patients with open fractures or diabetes were at higher risk. Tissue ischemia produced by a tourniquet did not appear to result in more wound healing or infectious complications. Level of Evidence: Level III, prognostic, comparative study